Under invoicing in the residential real estate market in Pakistan - Wahid, Abdul; Mantell, Edmund H.; Mumtaz, Muhammad Zubair (International Journal of Strategic Property Management, 2021)
In this paper the meaning of “under invoicing in a real estate market” signifies that the market value of real property exceeds its record value appearing in government documentation. The purpose of this study is to identify the level of under invoicing and determine the factors that affect the under invoicing in real estate markets in Pakistan. We apply OLS and Extreme Bounds Analysis techniques to test our propositions. The statistical sample consists of 338 real estate contracts. We find that under invoicing is determined by a multiplicity of factor. These include: the capital gains tax rate, the measurable amount of corruption in the economy, the risk-free rate, a buyer’s profession, the reputation of the local housing authority, and the degree of disequilibria in regional real estate markets. Our findings are consistent with four distinct hypotheses: (a) tax evasion hypothesis, (b) widening gap hypothesis, (c) a corruption hypothesis and (d) a signaling hypothesis. The evidence suggests that higher rates of taxation and a larger statistical incidence of corruption in markets tend to be associated with a greater probability of under-invoicing. The findings of the study have practical implications for those investors who are interested in real estate markets of emerging and developing economies. First published online 05 March 2021